2016
DOI: 10.1016/j.ijgo.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Progestin‐based contraceptive on the same day as medical abortion

Abstract: Objective To determine the success rate of medical abortion when a progestin-based contraceptive—either an etonogestrel implant or depot medroxyprogesterone acetate (DMPA) injection—is given on the same day as mifepristone for medical abortion. Methods In a retrospective chart review, data were assessed for women aged 15–49 years who underwent medical abortion (≤63 days of pregnancy) at two hospitals in KwaZulu Natal, South Africa, between August 2013 and July 2014. The women were given oral mifepristone (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In a retrospective study, Park et al [198] demonstrated that the administration of a progestin-based contraceptive such as an ENG implant or DMPA injection on the same day as mifepristone for medical abortion did not alter the successful abortion rates [198]. In a recent systematic review and meta-analysis, Schmidt-Hansen et al [199] showed that after abortion, the risk of subsequent unintended pregnancy was lower for patients treated with the etonogestrel implant simultaneously with mifepristone compared to delayed treatment both after three (risk ratio = 0.10; 95% CI, 0.01 to 1.94; p = 0.13) and six months (risk ratio = 0.22; 95% CI, 0.06 to 0.78; p = 0.02).…”
Section: Post-abortion Implant Placementmentioning
confidence: 99%
“…In a retrospective study, Park et al [198] demonstrated that the administration of a progestin-based contraceptive such as an ENG implant or DMPA injection on the same day as mifepristone for medical abortion did not alter the successful abortion rates [198]. In a recent systematic review and meta-analysis, Schmidt-Hansen et al [199] showed that after abortion, the risk of subsequent unintended pregnancy was lower for patients treated with the etonogestrel implant simultaneously with mifepristone compared to delayed treatment both after three (risk ratio = 0.10; 95% CI, 0.01 to 1.94; p = 0.13) and six months (risk ratio = 0.22; 95% CI, 0.06 to 0.78; p = 0.02).…”
Section: Post-abortion Implant Placementmentioning
confidence: 99%
“…52 Progesterone is necessary to induce the progesterone receptors, and different agonists and antagonists have been developed for progesterone receptors. The important applications of ligand that can interact with the PRs are hormone replacement therapy, 53 developing contraceptives, 54,55 maintaining or even ending pregnancy, [55][56][57][58] as well as developing medications for controlling breast cancers or uterus fibroids. 59,60 Human Epidermal Growth Factor Receptor 2 (HER2)…”
Section: Progesterone Receptormentioning
confidence: 99%